STRATEGI PROGRAM VOCATIONAL SCHOOL SEBAGAI CORPORATE SOCIAL RESPONSIBILITY DJARUM FOUNDATION - Dede Sulaeman (Universitas Mercu Buana, 2017)
PT. Djarum is able to stand and operate its business for many years amid tight competition of cigarette business and rapid pressures from both public and government policies. It clearly requires company's ability to run a series of reliable strategies. The distribution of Djarum Foundation CSR in the form of Vocational School Program is believed to be part of those strategies. The question is what factors owned by Vocational School program so that it can support PT. Djarum to survive and even expand its business to date? This study aims to determine the eminence of the Djarum Foundation Vocational School Program, its communication, and community's legitimacy of the program. Using qualitative descriptive approach with the constructivist paradigm, this research utilizes interview and literature study as the data collection technique, while case study is applied as its study design. The results of this study explain that the Vocational School program is a superior CSR program, not easily imitated, and achieves the level of sustaining survival. Vocational School program communications are also conducted effectively by selecting media, targets, message contents, and resource persons in accordance with the program and the products it produces. This is to strengthen the strategic position of Djarum Foundation at national and international level. The program has also gained community legitimacy as is reflected in community enthusiasm for the program, its impacts on the economic improvement of the Kudus community, and the appreciation of local and central government towards the Vocational School program. Keywords: CSR, Vocational School, Legitimacy, Sustaining Survival